Condensate Formation in Collisionless Plasma - Treumann, R. A.; Baumjohann, Wolfgang (Frontiers in Physics, 2021)
Particle condensates in general magnetic mirror geometries in high temperature plasma may be caused by a discrete resonance with thermal ion-acoustic background noise near mirror points. The resonance breaks the bounce symmetry, temporally locking the particles to the resonant wavelength. The relevant correlation length is the ion gyroradius applying to all particles with mirror points distributed along it.